Scientific Literacy Improvement Using Socio-Scientific Issues Learning - Adinda Arlin Husniyyah; Erman Erman; Tarzan Purnomo; Mohammad Budiyanto (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This study aimed to describe the improvement of scientific literacy after learning based on Socio-scientific Issues using the Problem-Based Learning model. Method: This study was analyzed quantitatively descriptively using N-Gain to determine the student's scientific literacy improvement. Using a one-group pre-posttest design, 29 undergraduate students of the science education department from a university in Indonesia participated in this pre-experimental study. The data was collected using an observation sheet of learning implementation and scientific literacy tests given before and after the learning. Finding: The results of this study showed that students' scientific literacy was improved after participating in learning based on Socio-scientific Issues using the Problem-Based Learning model. The scientific literacy was improved from (category low) in the pretest to (category medium) in the posttest, and the average N-gain score was 0,64 (medium category). Improving scientific literacy is also supported by the Socio-scientific Issues of learning using the Problem-Based Learning model implemented very well. Novelty: This study’s novelty was to describe each indicator of scientific literacy of the undergraduate students that was improved by using Socio-Scientific Issues in Problem-Based Learning. Hopefully, this study will be helpful for further research and give a solution for science teachers to improve students' scientific literacy.